Sideways - Payne, Alexander, 1961-; Giamatti, Paul.; Church, Thomas Haden; Madson, Virginia; Oh, Sandra, 1971-; Papamichael, Phedon; Kent, Rolfe; Pickett, Rex.; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2005)
Miles is a divorced man and a failed writer who teaches junior high English. He decides to take his best friend, somewhat famous actor Jack, on a weeklong drive through California's wine country. There they explore their failures and question their relationships. Jack, who is about to get married, has an affair with a woman and wonders whether he should call off his wedding. Miles questions whether or not he made the right choice while trying to form a relationship with the woman's best friend, a waitress at a restaurant that he frequents often when visiting that part of the country.
Originally released as a motion picture in 2004.
Based on the novel by Rex Pickett.
Special features: Full-length commentary by Paul Giamatti and Thomas Haden Church; 7 deleted scenes; behind-the- scenes featurette; theatrical trailer.
Director of photography, Phedon Papamichael ; editor, Kevin Tent ; music, Rolfe Kent ; costume designer, Wendy Chuck ; production designer, Jane Ann Stewart.
Paul Giamatti, Thomas Haden Church, Virgina Madson, Sandra Oh.
MPAA rating: R; for language, some strong sexual content and nudity.
Keywords: Male friendship -- California -- Drama; Vineyards -- California -- Drama; Man-woman relationships -- California -- Drama; Amistad -- California -- Teatro; Relaciones hombre-mujer -- Teatro; Feature films; Films for the hearing impaired; Comedy -- Feature; Adaptation -- Feature